2017
DOI: 10.1177/0954409717706251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the presence of moisture at the wheel–rail interface during dew and damp conditions

Abstract: Incidents involving low levels of adhesion between the wheel and rail are a recurrent issue in the rail industry. The problem has been mitigated using friction modifiers and traction enhancers, but a significant number of incidents still occur throughout the year. This study looks at the environmental conditions that surround periods of low adhesion in order to provide an insight into why low adhesion events occur. Network Rail Autumn data, which provided details on the time and location of low adhesion incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 8 publications
1
27
0
Order By: Relevance
“…This shows that iron oxides could play a role in low adhesion due to leaf layers, as well as throughout the year due to the wet-rail phenomenon. Previous analysis of Network Rail station overruns showed that during the autumn season, no railhead leaf contamination was seen for approximately 50 % of incidents as seen in Table 1 [7]. Table 1.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This shows that iron oxides could play a role in low adhesion due to leaf layers, as well as throughout the year due to the wet-rail phenomenon. Previous analysis of Network Rail station overruns showed that during the autumn season, no railhead leaf contamination was seen for approximately 50 % of incidents as seen in Table 1 [7]. Table 1.…”
Section: Introductionmentioning
confidence: 92%
“…Table 1. Incidents where contamination has been reported after an incident [7] Outside the autumn season, or in situations such as tunnels [8], low adhesion still occurs due to the wet-rail phenomenon so although organic contamination certainly results in low adhesion, there are many more incidents where organic contamination is unlikely to be present.…”
Section: Introductionmentioning
confidence: 99%
“…The high probabilities between 05:00 -10:00 and 20:00 -24:00 in Figure 3 and Figure 4 could be attributed to the dew on the track [28]. Generally, mixtures of leaves and a small amount of water decrease the friction coefficient dramatically [7].…”
Section: Incident Analysismentioning
confidence: 99%
“…Work carried out to analyse the frequency of the braking related incidents during the autumn period has shown that the cause is split 50:50 between leaves and 'wet-rail' syndrome [1]. Wet-rail syndrome relates to low adhesion caused by the presence of small amounts of water along with some solid material, such as oxides generated naturally in the wheel/rail interface.…”
Section: Introductionmentioning
confidence: 99%